The Roles of Parents for Children's Faith Education: A Catechization Review - Lukas Ahen; cenderato cenderato; Arius Arifman Halawa (Al-Albab, 2021)
This study aims to determine the extent to which parents at Stasi Santo Andreas Binjai, Parish of Santo Mikael Tanjung Baung, Sintang Diocese have played their role as educators of the faith of their children in the Industrial Revolution Era 4.0. This paper explores the obstacles faced by parents and how to overcome these obstacles to carry out their roles as faith educators for their children. This study uses a qualitative descriptive method that describes all the symptoms or conditions that exist. The data collection was conducted using three techniques: direct observation with observation guidance, direct communication through dialogue, and/or direct communication with participants to collect research data using tools (interview guides and documentary studies with visuals) during the study as evidence that researchers took to the field to conduct research. Based on the results, it is known that parents are not yet fully aware of their duties and responsibilities as the first and foremost faith educators for their children. Instead, the responsibility of fostering children's faith is mostly left to schools and churches as institutions (administrators of Stasi and Parish Churches). Lack of time for parents to be with their children and lack of understanding and awareness of parents about their duties and responsibilities in their children's faith education are inhibiting factors. The question exists, how to overcome the obstacles parents face as faith educators for their children. Many parents try to take advantage of family time (although it is limited) to give advice and practical teachings as a form of practical family catechesis, monitor children's activities, and encourage their children to take part in church activities.